Perbedaan Berpikir Kritis Siswa Menggunakan Bahan Ajar Lks Berbasis Model Berpikir Induktif dan Model Induktif Kata Bergambar pada Mata Pelajaran Ipa Kelas Iv Min 2 Kota Bengkulu - Azimah, Azimah (Yayasan Darusssalam Bengkulu, 2022)
This study aims to determine the differences in students' critical thinking using science worksheet teaching materials based on inductive thinking models with the Pictorial Word Inductive model in class IV MIN 2 Bengkulu City, differences in critical thinking from groups of students with high initial abilities using model-based science worksheets teaching materials inductive thinking with the Pictorial Word Inductive model in class IV MIN 2 Bengkulu City, differences in critical thinking from groups of students with low initial abilities using LKS IPA teaching materials based on inductive thinking models with the Pictorial Inductive Word model in class IV MIN 2 Bengkulu City, the interaction between learning model and initial ability to think critically in class IV MIN 2 Bengkulu City. This study uses a quantitative approach with a quasi-experimental research type. The subjects of this study were MIN 2 students, totaling 40 students. Data collection was carried out using an essay test. The results of the study showed 1) Overall there were differences in students' critical thinking between those taught using LKS teaching materials for science subjects based on inductive thinking learning models and those based on the Pictorial Word Inductive model. .2) there are differences in the critical thinking of students who have high initial abilities between those taught using LKS teaching materials for science subjects based on inductive thinking learning models and those based on the Pictorial Word Inductive model. 3) there is no difference in the critical thinking of students with low initial abilities between those taught using LKS teaching materials for science subjects based on inductive thinking learning models and pictorial word inductive models. 4) There is interaction between the learning model and prior knowledge of critical thinking skills students in science subjects at MIN 2 Bengkulu city.